Multispecies ethnography: reciprocal interaction between residents and the environment in Segara Anakan, Indonesia. (3rd July 2021) - Sanjatmiko, Prihandoko
ABSTRACT: This article argues that the anthropocentric perspective applied in the literature on humans and the environment has produced invalid, biased conclusions, which have caused errors in the measures taken to mitigate natural disasters. Taking the case of the residents of Kampung Laut, this study synergizes the concept of culture and nature. The residents live in an area facing landscape changes due to massive sedimentation. Their first problem is related to land tenure. The other relates to agricultural activities which require reciprocal interactions between humans and the environment in the ecological system. Kampung Laut residents, who once lived harmoniously with marine biota, must now adapt and cultivate new varieties of rice, mangroves and albizia. The result of this research reveals that the balance between humans and nature requires a cause and several forms of interaction such as threats, conflicts, compromises and harmony, which may occur simultaneously and not gradually. This article asserts that anthropology as science can contribute to humanitarian issues through a holistic and integrative multispecies understanding that enables humans and nature to develop a balanced and sustainable ecological system.